Six-wave interaction on resonant nonlinearity in a waveguide with infinitely conducting surfaces - Valery V. Ivakhnik; Darkhan R. Kapizov; Vladimir I. Nikonov (Физика волновых процессов и радиотехнические системы)
Background. When using six-wave radiation converters implemented in waveguides, in nonlinear adaptive optics systems, real-time image processing, it is necessary to know the correspondence between the complex amplitudes of the signal and object waves. Aim. Study of the intensity, spatial structure of pump waves, characteristics of the nonlinear medium influence on the quality of wavefront rotation during six-wave interaction on resonant nonlinearity in a waveguide with infinitely conducting surfaces. Methods. Using the expansion of interacting waves into waveguide modes, expressions for the point blur function of a six-wave radiation converter are obtained, which are analyzed numerically. Results. Assuming that one of the pump waves excites the zero mode of the waveguide, and the change in the amplitude of the other pump wave on the edge of the waveguide changes according to the Gaussian law, the dependences of the half-width of the central maximum of the modulus of the point blur function on the intensity of the single-mode pump wave, the width of the Gaussian pump wave, and the characteristics of the nonlinear medium are obtained. Conclusion. It is shown that the parameters of the nonlinear medium and the intensity of the single-mode pump wave have little effect on the quality of wavefront circulation. Reducing the width of the Gaussian pump wave improves the quality of wavefront circulation.